Coupling Relationship Between Densification Characteristics and Tight Oil Accumulation of the FGSR Reservoir: A Case Study of the Chang 7 Member of the Triassic Yanchang Formation in the Zhenyuan Area of the Southwest Ordos Basin, Central China - He, Weiling; Wang, Ruyue; Lyu, Qiqi; Liu, Jun; Wu, You (Frontiers in Earth Science, 2022)
Fine-grained sedimentary rock reservoirs (FGSRs) in a deep-water sedimentary environment from the Late Triassic Yanchang Formation in Ordos Basin in central China have huge potential for tight oil production. According to the comprehensive research of fluid inclusion experiment, scanning electron microscope, cathodoluminescence, the thin section identification and whole rock analysis, the petrographic characteristics, fluorescence spectrum parameters, the homogenization temperature of oil inclusions and associated brine inclusions in FGSRs reservoir were analyzed to explore the coupling relationship between densification characteristics and tight oil accumulation of the FGSRs reservoir. The results show the FGSRs reservoir diagenesis has experienced compaction, cementation and multiple stages of dissolution. A comprehensive analysis of burial history shows that Chang 7 Member FGSRs reservoir in the study area has three phases of oil charging, corresponding to the geologic time range of 132-124Ma, 120-102.0 Ma, and 98.0-97.0 Ma. The organic acid produced by the first stage oil charging accelerated the dissolution of feldspar and cuttings, and the dissolution pores increased significantly. Then, the organic acid in the second stage oil charging accelerated the dissolution, and the abnormally high hydrocarbon expulsion pressure inhibited the damage of compaction on the pores of FGSRs reservoir. Finally, the thermal evolution degree of source rocks reached the highest in the third stage oil charging. The constructive effect of large-scale organic acids on pores and the protective effect of chlorite membrane on pores inhibited densification process of the FGSRs reservoir. In short, the FGSRs reservoir has experienced a cyclical reservoir densification process of “reducing porosity-increasing porosity-preserving porosity”. The coupling of pore evolution and oil charging of the FGSRs reservoir is the key to the extensive accumulation and large-scale reservoir formation of tight oil in Chang 7 Member of Yanchang Formation in Zhenyuan area, southwest Ordos Basin. The signiﬁcance of the study may help to understand the process of the tight oil accumulation and predict tight oil of the FGSRs reservoir distribution.